A Facile Strategy to Prepare Shaped ZSM-5 Catalysts with Enhanced Para-Xylene Selectivity and Stability for Toluene Methylation: The Effect of In Situ Modification by Attapulgite - Yiren Wang; Yang Chang; Min Liu; Anfeng Zhang; Xinwen Guo (Molecules, 2019)
A general strategy for preparing shaped toluene methylation catalysts with enhanced para-selectivity and stability is developed by extruding ZSM-5 zeolite with attapulgite as a binder. The novel attapulgite/ZSM-5 extrudate exhibited significantly higher para-selectivity and stability in comparison to the conventional alumina-bound ZSM-5 extrudate. The catalyst samples have been characterized by in situ X-ray diffraction, scanning electron microscope (SEM), NH3 temperature programmed desorption (TPD), thermogravimetric analysis (TGA) as well as n-hexane/cyclohexane physical adsorption. The enhanced catalytic performance of attapulgite/ZSM-5 extrudate is correlated with the in-situ modification of acid sites in the catalyst by mobile alkaline species, which is introduced via extrusion with attapulgite. Moreover, a higher para-selectivity was obtained over attapulgite-bound modified ZSM-5 extrudate. Such facile and universal strategy of extruding ZSM-5 catalysts with attapulgite as binder could pave a way for preparation of shaped zeolite-base catalyst with enhanced catalytic performance.